76.7k views
5 votes
Solve the system by substitution.-5x—9y=33 -y—1=x

User Hathor
by
4.7k points

1 Answer

0 votes

The system of equations can be written as:

-5x - 9y = 33..............(1)

-y - 1 = x.......................(2)

This can be rewritten as:

x = - y - 1........................(2)

Substitute equation (2) into equation (1)

-5(-y - 1) - 9y = 33

5y + 5 - 9y = 33

9y - 5y = 5 - 33

4y = -28

y = -28 / 4

y = -7

Substitute the value of y into equation (2)

x = - y - 1

x = -(-7) - 1

x = 7 - 1

x = 6

User Chickens
by
4.4k points